Interaction between DMRT1 function and genetic background modulates signaling and pluripotency to control tumor susceptibility in the fetal germ line - Krentz, Anthony D. (2013)
Dmrt1(doublesex and mab-3 related transcription factor 1) is a regulator of testis development in vertebrates that has been implicated in testicular germ cell tumors of mouse and human. In the fetal mouse testis Dmrt1 regulates germ cell pluripotency in a strain-dependent manner. Loss of Dmrt1 in 129Sv strain mice results in a >90% incidence of testicular teratomas, tumors consisting cells of multiple germ layers; by contrast, these tumors have never been observed in Dmrt1 mutants of C57BL/6J (B6) or mixed genetic backgrounds. To further investigate the interaction between Dmrt1 and genetic background we compared mRNA expression in wild type and Dmrt1 mutant fetal testes of 129Sv and B6 mice at embryonic day 15.5 (E15.5), prior to overt tumorigenesis. Loss of Dmrt1 caused misexpression of overlapping but distinct sets of mRNAs in the two strains. The mRNAs that were selectively affected included some that changed expression only in one strain or the other and some that changed in both strains but to a greater degree in one versus the other. In particular, loss of Dmrt1 in 129Sv testes caused a more severe failure to silence regulators of pluripotency than in B6 testes. A number of genes misregulated in 129Sv mutant testes also are misregulated in human testicular germ cell tumors (TGCTs), suggesting similar etiology between germ cell tumors in mouse and man. Expression profiling showed that DMRT1 also regulates pluripotency genes in the fetal ovary, although Dmrt1 mutant females do not develop teratomas. Pathway analysis indicated disruption of several signaling pathways in Dmrt1 mutant fetal testes, including Nodal, Notch, and GDNF. We used a Nanos3-cre knock-in allele to perform conditional gene targeting, testing the GDNF coreceptors Gfra1 and Ret for effects on teratoma susceptibility. Conditional deletion of Gfra1 but not Ret in fetal germ cells of animals outcrossed to 129Sv caused a modest but significant elevation in tumor incidence. Despite some variability in genetic background in these crosses, this result is consistent with previous genetic mapping of teratoma susceptibility loci to the region containing Gfra1. Using Nanos3-cre we also uncovered a strong genetic interaction between Dmrt1 and Nanos3, suggesting parallel functions for these two genes in fetal germ cells. Finally, we used chromatin immunoprecipitation (ChIP-seq) analysis to identify a number of potentially direct DMRT1 targets. This analysis suggested that DMRT1 controls pluripotency via transcriptional repression of Esrrb, Nr5a2/Lrh1, and Sox2. Given the strong evidence for involvement of DMRT1 in human TGCT, the downstream genes and pathways identified in this study provide potentially useful candidates for roles in the human disease.